Seroepidemiology of Plasmodium species infections in Zimbabwean population. (December 2016) - Amanfo, Seth; Mduluza, Takafira; Midzi, Nicholas; Cavanagh, David; Mutapi, Francisca
Abstract Background Individuals living in malaria-endemic regions may be exposed to more than onePlasmodium species; there is paucity of data on the distribution of the different species ofPlasmodium in affected populations, in part due to the diagnostic method of microscopy, which cannot easily differentiate between the species. Sero-epidemiological data can overcome some of the shortcomings of microscopy. Methods The specificity of IgG antibodies to recombinant merozoite surface protein 1 (MSP-119 ) derived from four humanPlasmodium species (Plasmodium falciparum, Plasmodium vivax, Plasmodium malariae, Plasmodium ovale ) was investigated using competition enzyme-linked immunosorbent assay. Subsequently, these antigens were used to determine the exposure prevalence to the differentPlasmodium species in serum samples of participants. One-hundred individuals, aged five-18 years, from each of the threePlasmodium meso-endemic Zimbabwean villages (Burma Valley, Mutoko, Chiredzi) were recruited in the study. Results The study demonstrated that the host serum reactivity to MSP-119 antigens was species-specific and that no cross-reactivity occurred. The overall prevalence of antibody response to MSP-119 antigens was 61 % in Burma Valley, 31 % in Mutoko and 32 % in Chiredzi. Single species IgG responses to MSP-119 were most frequent againstP .falciparum, followed byP .malariae andP .ovale, with responses toP .vivax being the least prevalent. Interestingly, 78–87 and 50 % of sera with IgG responses toP .malariae andP .ovale MSP-119, respectively, also had IgG specific response forP .falciparum MSP-119 antigens, indicating that exposure to these species is a common occurrence in these populations. Single species IgG responses to the non-falciparum species were at a very low frequency, ranging between 0 and 13 % forP .malariae . Conclusions There is evidence of a higher exposure to the non-falciparum parasite species than previously reported in Zimbabwe. The recombinant MSP-119 antigens could be used as additional diagnostic tools in antibody assays for the detection of exposure to the differentPlasmodium species. The results also introduce an interesting concept of the co-infection of non-falciparumPlasmodium almost always withP. falciparum, which requires further validation and mechanistic studies.